Immunoglobulin light chain allelic inclusion in systemic lupus erythematosus. Issue 8 (24th June 2015) - Fraser, Louise D.; Zhao, Yuan; Lutalo, Pamela M. K.; D'Cruz, David P.; Cason, John; Silva, Joselli S.; Dunn‐Walters, Deborah K.; Nayar, Saba; Cope, Andrew P.; Spencer, Jo
<x xml:space="preserve">Abstract</x> The principles of allelic exclusion state that each B cell expresses a single light and heavy chain pair. Here, we show that B cells with both kappa and lambda light chains (Igκ and Igλ) are enriched in some patients with the systemic autoimmune disease systemic lupus erythematosus (SLE), but not in the systemic autoimmune disease control granulomatosis with polyangiitis. Detection of dual Igκ and Igλ expression by flow cytometry could not be abolished by acid washing or by DNAse treatment to remove any bound polyclonal antibody or complexes, and was retained after two days in culture. Both surface and intracytoplasmic dual light chain expression was evident by flow cytometry and confocal microscopy. We observed reduced frequency of rearrangements of the kappa‐deleting element (KDE) in SLE and an inverse correlation between the frequency of KDE rearrangement and the frequency of dual light chain expressing B cells. We propose that dual expression of Igκ and Igλ by a single B cell may occur in some patients with SLE when this may be a consequence of reduced activity of the KDE.